Africa Now! Emerging Issues and Alternative Perspectives (Springer International Publishing, 2018)
This book presents relevant and timely endogenous procedures for addressing the challenge of transforming ideas into sustainable opportunities in Africa. It explores how Africa could be understood in the context of emerging global realities, providing alternative frameworks that will not just be participatory in conception and practice, but equally show a contextual workability for the varying aspects of the developmental enterprise in Africa. Despite having alternative and less cumbersome sources of funding, with commendable economic growth indices, and several economies among the fastest growing globally, African countries have been unable to transmute related opportunities into sustainable human development outcomes for majority of its citizenry. Over four rich sections the authors cover subjects ranging from environment and natural resource management, to governance, economy and sustainable development. The book continues with a section on Education and Human Development and a case study in transnationalism. The final section discusses crime, conflict and regional dynamics, including highly disputed topics such as forced migration and sex trade. This indispensable resource will be of great use to students and researches globally in fields such as sociology, anthropology, environmental studies, politics and economics with a focus on contemporary Africa, as well as to policy planners and human rights activists invested in the future development of Africa.